The effect of guselkumab on inhibiting radiographic progression in patients with active psoriatic arthritis: study protocol for APEX, a Phase 3b, multicenter, randomized, double-blind, placebo-controlled trial - Christopher T. Ritchlin; Laura C. Coates; Philip J. Mease; Désirée van der Heijde; Jiao Song; Yusang Jiang; May Shawi; Alexa P. Kollmeier; Proton Rahman (Trials, 2023)
Abstract Background Guselkumab, a fully human monoclonal antibody targeting the interleukin (IL)-23p19 subunit, is approved to treat adults with active psoriatic arthritis (PsA). In the Phase 3 DISCOVER-2 trial of 739 bilogico-naïve patients with active PsA, guselkumab 100 mg resulted in less radiographic progression, assessed via change from baseline in PsA-modified van der Heijde-Sharp (vdH-S) score, compared with placebo at week (W) 24 when given at W0, W4, and then every 4 weeks (Q4W) or Q8W. The least squares mean differences from placebo were -0.66 for guselkumab Q4W (p=0.011) and -0.43 for guselkumab Q8W (p=0.072). Reports suggest baseline C-reactive protein (CRP) and joint erosions are strongly prognostic of poor outcomes, especially radiographic progression, in PsA patients. We designed a trial (APEX) to further assess the effect of guselkumab on radiographic progression in patients with active PsA and risk factors for radiographic progression. Methods Patients are eligible for APEX if they have had PsA for ≥6 months and active disease (≥3 swollen and ≥3 tender joints, CRP ≥0.3 mg/dL) despite prior therapy with conventional synthetic disease-modifying antirheumatic drugs, apremilast, and/or nonsteroidal anti-inflammatory drugs, with ≥2 joints with erosions on baseline radiographs (hands and feet). The primary and major secondary endpoints are the proportion of patients achieving ≥20% improvement in American College of Rheumatology response criteria (ACR20) response at W24 and change from baseline at W24 in PsA-modified vdH-S score, respectively. Sample sizes of 350/250/350 for guselkumab Q8W/guselkumab Q4W/placebo are expected to provide >99% power to detect significant differences in W24 ACR20 response rates for each guselkumab group vs placebo, as well as ≥90% (Q4W vs placebo) and ≥80% (Q8W vs placebo) power to detect a significant difference in PsA-modified vdH-S score change at W24. A Cochran-Mantel-Haenszel test and analysis of covariance will compare treatment efficacy for the primary and major secondary endpoints, respectively. Discussion DISCOVER-2 findings informed the design of APEX, a Phase 3b study intended to further evaluate the impact of guselkumab in patients with active PsA and known risk factors for radiographic progression. Trial registration This trial was registered at ClinicalTrials.gov, NCT04882098 . Registered on 11 May 2021.